Protokol Pemeriksaan Mental pada Pelaku Pembunuhan dan Implikasinya dalam Investigasi Forensik - Syahla Marsellita Wahyudi; Annisa Salmaadani Syafitri; Fiza Afifah; Insan Anshori Umma; Lale Nandita Hulfifa; Kezia Michella Yusak M (Lembaga Pengembangan Kinerja Dosen, 2026)
Homicide cases involve complex legal, social, and psychological dimensions that require comprehensive investigation procedures. Besides collecting physical evidence, understanding the mental condition of offenders is essential to identify motives, behavioral patterns, and the extent of criminal responsibility. This study aims to examine the contribution of mental examination protocols in supporting homicide investigations from a forensic psychological perspective. A literature review approach was employed by analyzing relevant scientific publications discussing homicide, forensic assessment, psychological evaluation, and offender profiling. The review indicates that homicidal behavior may emerge from the interaction of personal, social, environmental, and psychological factors. Various assessment methods, including personality testing, structured and semi-structured interviews, affective disorder evaluation, neuropsychological assessment, memory examination, and trauma-related assessment, are frequently utilized to obtain a comprehensive understanding of an offender’s mental state. The findings suggest that mental examination not only assists in evaluating psychological functioning but also contributes to criminal profiling and legal decision-making. The integration of forensic psychological assessment into homicide investigations may strengthen the objectivity of investigative processes and provide a broader understanding of factors underlying violent criminal behavior.